2019
DOI: 10.1093/ajcn/nqz095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diets enriched in stearic, oleic, and palmitic acids on inflammation, immune response, cardiometabolic risk factors, and fecal bile acid concentrations in mildly hypercholesterolemic postmenopausal women—randomized crossover trial

Abstract: Background Direct comparisons between SFAs varying in chain length, specifically palmitic acid (16:0) and stearic acid (18:0), relative to the latter's metabolic product, oleic acid (18:1), on cardiometabolic risk factors are limited. Objective The aim of this study was to determine the relative comparability of diets enriched in palmitic acid, stearic acid, and oleic acid on inflammation and coagulation markers, T lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 67 publications
1
60
0
2
Order By: Relevance
“…The concentrations of TAG did not differ between the diets [15][16][17][18][19][20][21][22][23][24], except in one study, where the TAG concentrations were lower after an interesterified stearic acid-rich diet [12]. However, the majority of studies found lower TC concentrations on the stearic acid-rich diet as compared with palmitic acid [15][16][17][18][19][20]23]. In five of these studies, LDL-C concentrations were also decreased [16][17][18]20,23], and in two studies the concentration of LDL-C tended to be lower on stearic acid [12,19].…”
Section: Lipids and (Apo) Lipoproteinsmentioning
confidence: 93%
See 4 more Smart Citations
“…The concentrations of TAG did not differ between the diets [15][16][17][18][19][20][21][22][23][24], except in one study, where the TAG concentrations were lower after an interesterified stearic acid-rich diet [12]. However, the majority of studies found lower TC concentrations on the stearic acid-rich diet as compared with palmitic acid [15][16][17][18][19][20]23]. In five of these studies, LDL-C concentrations were also decreased [16][17][18]20,23], and in two studies the concentration of LDL-C tended to be lower on stearic acid [12,19].…”
Section: Lipids and (Apo) Lipoproteinsmentioning
confidence: 93%
“…In five of these studies, LDL-C concentrations were also decreased [16][17][18]20,23], and in two studies the concentration of LDL-C tended to be lower on stearic acid [12,19]. Lower HDL-C concentrations on the stearic acid-rich diet were found in three studies [17,19,20], while in seven other studies, no significant differences were found [12,16,18,[21][22][23][24]. No changes in concentrations of very-low density lipoprotein (VLDL)-C were reported [17,19,20].…”
Section: Lipids and (Apo) Lipoproteinsmentioning
confidence: 94%
See 3 more Smart Citations